2011
DOI: 10.1111/j.1530-9290.2011.00353.x
|View full text |Cite
|
Sign up to set email alerts
|

Application of Product Data Technology Standards to LCA Data

Abstract: Applications of information and communications technology (ICT) for the management of environmental data, if used during the design and at the end of the product life cycle, can improve the environmental performance of products. This specific application of ICT for data management is called product data technology (PDT) and is based on the use of international standards developed by ISO TC184/SC4. PDT enables the computerized representations of information about products, processes, and their properties that a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 5 publications
0
11
0
Order By: Relevance
“…Information standards based on product data technology standards for LCA data have been proposed [35]. Expanding these arguments to blockchain, as an information delivery vehicle with appropriate models developed, is natural.…”
Section: Eco-design and Lcamentioning
confidence: 99%
“…Information standards based on product data technology standards for LCA data have been proposed [35]. Expanding these arguments to blockchain, as an information delivery vehicle with appropriate models developed, is natural.…”
Section: Eco-design and Lcamentioning
confidence: 99%
“…Moreover, the knowledge acquired during product development can be used to improve the product over time. Similarly, Moreno et al (2011) argued that the use of information technology embedded in a product can reduce environmental impact of a product's development over its life cycle. According to a review by Rouibah and Caskey (2003), there are few studies related to change management within enterprises.…”
Section: Resultsmentioning
confidence: 97%
“…In this way, PLM incorporates the knowledge acquired during product development to all stages of the product's life (Brigatini and Miguel 2009). Moreno et al (2011) suggested that information technology embedded in the product could be used to obtain useful information that could guide the proposal and development of product changes and reduce the environmental impact of the product over its life cycle. In a review of the literature related to this, Rouibah and Caskey (2003) found that there are only a few studies related to the management of product change across multiple enterprises.…”
Section: Macdonnel and Cleggmentioning
confidence: 99%
“…This calls for attention and preparation for all domains involved in the AEC industry, including the manufacturers. Figure 3 The technical roadmap for product support (Pauwels et al, 2017) Numerous studies collected for this review adopted the definition of an ontology as a 'formal, explicit specification of a shared conceptualization', that provides a shared vocabulary that can be used to model semantic information effectivity (Niknam et al, 2019, Costa and Madrazo, 2015, Moreno et al, 2011, Lu et al, 2015, Costa Jutglar, 2017. Thus, ontologies have the potential to enrich the semantics of product geometry as well as express the semantics of product data unambiguously.…”
Section: Benefits Of the Semantic Web And Linked Data Technologiesmentioning
confidence: 99%